The role of ultrasound in predicting non-invasive ventilation outcomes: a systematic review - Kheir, Matthew; Dong, Vincent; Roselli, Victoria; Mina, Bushra (Frontiers in Medicine, 2023)
Purpose: To systematically review and compare ultrasonographic methods and their utility in predicting non-invasive ventilation (NIV) outcomes. Methods: A systematic review was performed using the PubMed, Medline, Embase, and Cochrane databases from January 2015 to March 2023. The search terms included the following: ultrasound, diaphragm, lung, prediction, non-invasive, ventilation, and outcomes. The inclusion criteria were prospective cohort studies on adult patients requiring non-invasive ventilation in the emergency department or inpatient setting.Results: 15 studies were analyzed, which comprised of 1,307 patients (n= 942 for lung ultrasound score studies; n = 365 patients for diaphragm dysfunction studies). Lung ultrasound scores (LUS) greater than 18 were associated with NIV failure with a sensitivity 62-90.5% and specificity 60-91.9%. Similarly, a diaphragm thickening fraction (DTF) of less than 20% was also associated with NIV failure with a sensitivity 80-84.6% and specificity 76.3-91.5%.Conclusions: Predicting NIV failure can be difficult by routine initial clinical impression and diagnostic work up. This systematic review emphasizes the importance of using lung and diaphragm ultrasound, in particular the lung ultrasound score and diaphragm thickening fraction respectively, to accurately predict NIV failure, including need for ICU-level of care, invasive mechanical ventilation, and higher rates of mortality.